Effect of self‐assembling peptide P11‐4 on enamel erosion: AFM and SEM studies. Issue 4 (5th October 2015) - Ceci, Matteo; Mirando, Maria; Beltrami, Riccardo; Chiesa, Marco; Colombo, Marco; Poggio, Claudio
Summary: The aim of the present in vitro study was to evaluate the protective effect of self‐assembling peptide P11 ‐4 (Curodont™ Protect/Credentis) on enamel erosion produced by a soft‐drink, by using Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Thirty human incisors were equally and randomly assigned to 6 groups. Group 1: intact enamel, group 2: soft drink, group 3: Curodont ™ Protect applied, group 4: Curodont ™ Protect applied + soft drink, group 5: soft drink + Curodont ™ Protect applied, group 6: soft drink + Curodont ™ Protect applied + soft drink. Specimens were observed through atomic force microscopy (AFM). The root mean‐square roughness (Rrms) was obtained from the AFM images and the differences in the averaged values among the groups were analyzed by Shapiro–Wilk test in order to assess the normality of the distribution. Parametric ANOVA and post hoc Tuckey test were performed to assess the differences between the different groups. After demineralization process, enamel demonstrated a high degree of surface porosity. This morphological aspect was reflected in the increase of Rrms values. No significant differences (p > 0.05) were reported between intact enamel and enamel only treated with P11 ‐4 and between eroded enamel and enamel treated with P11 ‐4 and then demineralized. However significant differences (p < 0.05) were recorded when comparing softened enamel with softened enamel further remineralized with biomimetic self‐assembling peptides and enamel treated with the protective paste between two acid attacks. The use of P11 ‐4 remineralizing may offer a degree of protection from enamel erosion. SCANNING 38:344–351, 2016. © 2015 Wiley Periodicals, Inc.